USE OF IMAGE MAP, FRAME AND MULTIMEDIA FLASH TARGET IN DESIGNING A HOMEPAGE USING HTML - Abrar Khaled Ali; Ir. Aqwam Rosadi Kardian. MM Ir. Aqwam Rosadi Kardian. MM (Jurnal Sistem Informasi, 2002)
World Wide Web is built from a Web Page or known as the Home Page. While theirown home page created using HTML language.To create a Home Page that was good and interesting, of course, we try in any waygive a different look than usual, so that makes it look more alive and creating formsan interesting link to be clicked.No escape from making a link, the writer here tries to minimize access time /download from users that is by making an image that can be divided into several linkcalled with Image Map and Target Frame to make users more easily search and findcontents of the home page without having to return to the main menu so that it cansave time appearance on a home page.